Konformitas teman sebaya dan perilaku bullying remaja berbasis Teori Adaptasi Roy - Rina Maisaroh; Sri Mulyani; Siti Patonah (JOURNAL OF Community Health Issues, 2026)
Background: Adolescence is a transitional developmental phase that is strongly influenced by the social environment, particularly peer groups. At SMPN 1 Trucuk, bullying has become a serious concern following an incident of violence that caused physical and psychological harm to a student. One factor potentially associated with bullying behavior is peer conformity, defined as the tendency of adolescents to adjust their attitudes and behavior to group norms in order to gain social acceptance. From the perspective of Roy's Adaptation Theory, social pressure may function as an environmental stimulus that influences adolescents' adaptive responses. Purpose: To analyze the relationship between peer conformity and bullying behavior among adolescents at SMPN 1 Trucuk. Method: This study employed a cross-sectional design. The population consisted of 181 seventh-grade students, with a sample of 125 respondents selected using simple random sampling. The independent variable was peer conformity, while the dependent variable was bullying behavior. Data were collected using questionnaires and analyzed using the Spearman's Rho test with a significance level of α < 0.05. Results: Most respondents demonstrated a moderate level of peer conformity (68.8%). Meanwhile, the majority of respondents demonstrated a high level of bullying behavior (82.4%). The Spearman's Rho analysis yielded a p-value of 0.036 (α < 0.05) and a correlation coefficient of 0.188. These findings indicate a statistically significant positive relationship between peer conformity and bullying behavior among adolescents, with a weak correlation strength. Conclusion: There was a statistically significant relationship between peer conformity and bullying behavior among adolescents. Adolescents are encouraged to develop positive adaptive responses within their peer environment. Teachers should strengthen character education and create a supportive school environment, while parents are encouraged to provide effective communication, guidance, and emotional support for their children.